2010
DOI: 10.1016/j.ijscr.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of colonic carcinoma, renal cell carcinoma and gastrointestinal stromal tumour—A case report

Abstract: The occurrence of synchronous primary neoplasms remains an issue of great interest to surgeons and oncologists in particular, and the medical field in general. The question of common genetic pathways in the pathogenesis of such neoplasms is always raised when such associations are seen-whether metachronously or synchronously. The possibility of the coexistence of multiple tumours in the same patient must be taken into consideration when preparing patients for operation and a thorough search of the intraperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Czene and Hemminki's study demonstrates unequivocally that individuals with RCC face an increased risk of developing additional malignancies not only during the first year following the main diagnosis but also after > 10 years [ 21 ]. A rare case of coexistence of three neoplasms (colonic carcinoma, renal cell carcinoma, and gastrointestinal stromal tumor) in a single patient has been reported [ 22 ]. It is suggested that microsatellite instability testing may be used in all patients presenting with colorectal and urological cancers to detect a common genetic aberration between malignancies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Czene and Hemminki's study demonstrates unequivocally that individuals with RCC face an increased risk of developing additional malignancies not only during the first year following the main diagnosis but also after > 10 years [ 21 ]. A rare case of coexistence of three neoplasms (colonic carcinoma, renal cell carcinoma, and gastrointestinal stromal tumor) in a single patient has been reported [ 22 ]. It is suggested that microsatellite instability testing may be used in all patients presenting with colorectal and urological cancers to detect a common genetic aberration between malignancies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of MPNs is still unclear and is generally considered to be the result of multiple carcinogenic factors. Possible etiologies include genetic defects [7,8], medical treatment-related factors [9], environmental factors [10], and unhealthy living habits [11]. Pickled foods contain N-nitrosodimethylamine and other volatile N-nitroso compounds that show mutagenicity and carcinogenicity [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathogenesis of multiple primary malignancies are complex. Possible etiology include genetic, environmental, hormonal, medical treatment-related, and gender specific factors [10] . Moreover, the common genetic and environmental risk factors that were found in different cancers might increase the risk of multiple primary malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some reports demonstrated that CRC is associated with other primary malignancies, such as pancreatic carcinoma [5] , [6] , prostate cancer [7] , and renal carcinoma [4] , [8] , [9] . Burgess et al [10] reported a case that a patient with colonic carcinoma, renal cell carcinoma, and gastrointestinal stromal tumor. Capilna et al [11] described a female patient presented with primary malignancies of the fallopian tube, endometrium and sigmoid colon synchronously.…”
Section: Introductionmentioning
confidence: 99%